2008
DOI: 10.1002/cbf.1485
|View full text |Cite
|
Sign up to set email alerts
|

4‐Amino‐3‐acetylquinoline‐induced apoptosis of murine L1210 leukemia cells involves ROS‐mitochondrial‐mediated death signaling and activation of p38 MAPK

Abstract: Quinolines are known to be multitarget agents with a broad spectrum of biological activity. In a previous study, we showed that newly prepared 4-amino-3-acetylquinoline (AAQ) possesses strong anticancer activities. In this study, we investigated whether AAQ has cytotoxicity in murine L1210 leukemia cells. Results from cell proliferation assays showed that AAQ caused significant decrease in cell number in a dose-dependent manner. The cell death induced by AAQ appeared to involve apoptosis, based on evidence fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Numerous researchers have shown that ROS relate to apoptosis that is processed through the mitochondrial pathway, which depends on the activation of p38 (Figure 2) [40][41][42][43][44] . Apoptosis signal-regulating kinase 1 (ASK1) is an evolutionarily conserved mitogenactivated protein 3-kinase that activates both JNK and p38 MAPK, which may also be triggered by ROS [45][46][47][48][49] .…”
Section: Ros Involve Apoptosis That Relates To the P38 Pathwaymentioning
confidence: 99%
“…Numerous researchers have shown that ROS relate to apoptosis that is processed through the mitochondrial pathway, which depends on the activation of p38 (Figure 2) [40][41][42][43][44] . Apoptosis signal-regulating kinase 1 (ASK1) is an evolutionarily conserved mitogenactivated protein 3-kinase that activates both JNK and p38 MAPK, which may also be triggered by ROS [45][46][47][48][49] .…”
Section: Ros Involve Apoptosis That Relates To the P38 Pathwaymentioning
confidence: 99%
“…Several researchers have shown that ROS related apoptosis is processed by the mitochondrial pathway, through the activation of p38 [ 73 , 74 , 75 ]. It has been demonstrated that ROS-dependent activation of MAPKs is crucial for mitochondria-mediated apoptosis [ 76 ].…”
Section: Role Of Ros and Hne In The Hallmarks Of Cancermentioning
confidence: 99%
“…Substituted tetrahydroquinolins are important structures present in a wide variety of natural alkaloids and synthetic analogues with high biological activity as potent antitumour agents [ 93 , 94 ]. Amino-quinoline derivatives have been reported to have antiproliferative activity due to their ability to induce mitochondrial dysfunction by increasing ROS levels in the sensitive cervical epithelioid carcinoma cell line HeLaS3 and in the multi-drug resistant human cervical cancer KB-vin cell line [ 95 , 96 ].…”
Section: Chiral Analogues Of Natural Compounds With Stereospecific Cy...mentioning
confidence: 99%